Цветовая температура как модулятор визуального восприятия еды; Невская фотоника-2025 - Черкашина А. А. Алина Александровна; Коржнева Т. Г. Татьяна Геннадьевна; Туранов С. Б. Сергей Борисович; Толкачёва К. П. Ксения Петровна (2025, 2025)
Заглавие с экрана